Birth plans—Impact on mode of delivery, obstetrical interventions, and birth experience satisfaction: A prospective cohort study. Issue 1 (2nd November 2017) - Afshar, Yalda; Mei, Jenny Y.; Gregory, Kimberly D.; Kilpatrick, Sarah J.; Esakoff, Tania F.
Abstract: Objective: To examine whether the presence of a birth plan was associated with mode of delivery, obstetrical interventions, and patient satisfaction. Methods: This was a prospective cohort study of singleton pregnancies greater than 34 weeks' gestation powered to evaluate a difference in mode of delivery. Maternal characteristics, antenatal factors, neonatal characteristics, and patient satisfaction measures were compared between groups. Differences between groups were analyzed using chi‐squared for categorical variables, Fisher exact test for dichotomous variables, and Wilcoxon rank sum test for continuous or ordinal variables. Results: Three hundred women were recruited: 143 (48%) had a birth plan. There was no significant difference in the risk of cesarean delivery for women with a birth plan compared with those without a birth plan (21% vs 16%, adjusted odds ratio [adjOR] 1.11 [95% confidence interval (CI) 0.61‐2.04]). Women with a birth plan were 28% less likely to receive oxytocin ( P < .01), 29% less likely to undergo artificial rupture of membranes ( P < .01), and 31% less likely to have an epidural ( P < .01). There was no difference in the length of labor ( P = .12). Women with a birth plan were less satisfied ( P < .01) and felt less in control ( P < .01) of their birth experience than those without a birth plan. Conclusion: Women with and without a birth plan had similar odds of cesarean delivery. Though they had fewer obstetrical interventions, they were less satisfied with their birth experience, compared with women without birth plans. Further research is needed to understand how to improve childbirth‐related patient satisfaction.